(untitled) (Baghdad Science Journal, 2022)
Gingival crevicular fluid (GCF) may reflect the events associated with orthodontic tooth movement. Attempts have been conducted to identify biomarkers reflecting optimum orthodontic force, unwanted sequallea (i.e. root resorption) and accelerated tooth movement. The aim of the present study is to find out a standardized GCF collection, storage and total protein extraction method from apparently healthy gingival sites with orthodontics that is compatible with further high-throughput proteomics. Eighteen patients who required extractions of both maxillary first premolars were recruited in this study. These teeth were randomly assigned to either heavy (225g) or light force (25g), and their site specific GCF was collected at baseline and after 1hr, 1day, 7days, 14days, 21days and 28days post force application. Periostrips were used for GCF collection and subsequent phosphate buffered saline (PBS) was used for immediate protein elution with centrifugal speed of 10000rpm for 5min and stored at -80°C. Protein concentration was estimated using Bradford colorimetric assay. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) was carried out to resolve the purity of proteins in the collected samples and the method of collection was validated by western immuno-blotting of alpha amylase salivary enzyme. The current collection, storage and protein extraction protocol showed the best protein recovery and purity with validated collection free of salivary contamination. In conclusion, tiny GCF volume from healthy sites and evaporation issues of such promising non-invasive fluid motivate us to investigate a standardized protocol enabling optimal preservation of GCF sample and the currently followed protocol may serve as a reference for future proteomic studies searching for GCF biomarkers in diagnosing and monitoring orthodontic tooth movement.